Optimalisasi Pengadaan Dan Pemeliharaan Alat Kesehatan Untuk Meningkatkan Pelayanan Di Rsud Pagelaran Kabupaten Cianjur - Sikki, Nurhaeni; Nahuri, Sasinta Bela; Lestari, De Luh Pratiwi Angganing; Darmawan, Widiyah; Assegaf, Muhammad Iqbal; Fansari, Riska Fitriani Zenab; Putri, Aulia Salsabila; Wibawa, Made Sabda Adi; Puspita, Nike (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Quality healthcare requires the availability and optimal condition of medical devices. This study aimed to describe the medical device procurement and maintenance system at Pagelaran Regional General Hospital (RSUD Pagelaran) in Cianjur Regency and to identify supporting and inhibiting factors in its optimization. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document reviews. The results showed several constraints, including suboptimal procurement planning, limited budget, and a lack of skilled human resources in medical equipment maintenance. This study recommends optimization strategies, including needs-based planning improvements, enhanced human resource competency, utilization of information technology to monitor the use and maintenance of medical devices.